Developing SINJAWA: An Augmented Reality Pop-Up Book to Improve Javanese Script Writing in Elementary Students - Rita Damayanti; Sri Sukasih (AL-ISHLAH: Jurnal Pendidikan, 2025)
Students’ low proficiency in writing Javanese script remains a significant challenge in Javanese language instruction at SD Negeri 1 Grantung, Purbalingga Regency. This issue is largely attributed to students’ difficulties in mastering script forms and the limited use of varied and engaging instructional media. Therefore, innovative learning media are needed to improve students’ writing skills. This study aimed to develop and evaluate the effectiveness of the SINJAWA Pop-Up Book integrated with augmented reality (AR) in improving fifth-grade students’ Javanese script writing skills. The research employed a research and development (RD) approach based on the ADDIE model. Participants included 25 fifth-grade students, consisting of six students in a small-group trial and 19 students in a large-group trial, as well as classroom teachers and material and media experts. Data were collected through observation, interviews, documentation, questionnaires, and pretest–posttest assessments. Data analysis involved feasibility validation, practicality analysis, normality testing, and N-Gain analysis. The validation results indicated that the learning media were highly feasible, with scores of 94.28% from material experts and 91.66% from media experts. Practicality assessment showed very positive responses from students (95.2%) and teachers (93.33%). Learning outcomes improved significantly, as reflected by an N-Gain score of 74.48%, categorized as effective. The SINJAWA Pop-Up Book integrated with AR is a feasible, practical, and effective learning medium for enhancing fifth-grade students’ Javanese script writing skills.